Determinan Pajak Hotel, Pajak Restoran, Pajak Hiburan dan Pajak Reklame Terhadap PAD Se-Pulau Lombok Tahun 2019-2023 - Baiq Nindria Riguna Umarta; Endang Astuti; Iwan Harsono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the effect of hotel tax, restaurant tax, entertainment tax, and advertisement tax on Local Own-Source Revenue (PAD) in regencies/cities of Lombok Island. The background of this research is based on the importance of optimizing local taxes to enhance regional fiscal independence. The objective of this study is to analyze the partial and simultaneous effects of these tax variables on PAD. This research employs a quantitative approach using panel data regression analysis. The data used are secondary data from 2019–2023 obtained from official institutions. The selected model is the Fixed Effect Model (FEM) based on model selection tests. The results indicate that hotel tax and restaurant tax have a positive and significant effect on PAD. Meanwhile, entertainment tax and advertisement tax do not have a significant effect on PAD. Restaurant tax is identified as the most dominant variable influencing PAD. These findings suggest that tourism and consumption sectors play an important role in increasing regional revenue. In conclusion, optimizing hotel and restaurant taxes can be an effective strategy to improve PAD in Lombok Island.